Effect of silicon and pesticides in soil fertility and rice yield. - Furcal-Beriguete, Parménides (2013)
The objective of this work was to evaluate theeffect of silicon on the soil fertility, the incidence of diseasesand insect pests, the yield and quality of rice grains, varietyCR 4477. The study was conducted in La Vega, Florencia,San Carlos, Costa Rica between May and Octuber in 2010and 2011 in the same field. Five treatments were established:silicon to soil, silicon to soil plus pesticides (chemical alternatives),silicon to foliage, silicon to foliage plus pesticidesand a commercial control. Sources were silicon powder at70% of SiO2 applied 15 days before sowing at a dose of 100kg SiO2/ha and 40% SiO2 and 36% MgO concentrated liquidapplied to the foliage at a dose of 4 l/ha at 17 and 30 daysafter planting. The soil was an alluvial formation inceptisolorder, and at the beginning of the experiment had a pH of4.9, P and Si values of 29 and 44.7 ppm respectively, exchangeableacidity 1.2 cmol(+)/l and base sum 19.11 cmol(+)/l.The results showed no effect of silicon in soil fertility, the incidenceof pests and diseases, and milling quality, except thatthe combination of silicon applied at soil and the pesticidesused increased the zinc and copper content in the soil, alsothe zinc and magnesium in the leaves of rice, but this effectdid not result in yield and grain quality. Results also suggestthat the use of pesticides positively influenced weight andpaddy yield (p ≤ 0.05).